Excellent low-field magnetoresistance effect in Ga-doped MnZn ferrites - Hyo-Jin Kim; Sang-Im Yoo (AIP Advances, 2014)
An excellent low field magnetoresistance (LFMR) property was achieved from the Ga-doped (Mn0.8Zn0.2)Fe2O4 (MnZn) ferrites at room temperature (RT). For this study, undoped and Ga-doped MnZn ferrites with the nominal compositions of (Mn0.8Zn0.2)1−xGaxFe2O4 (x = 0 ∼ 0.1) were prepared by the conventional solid state reaction at 1400°C for 2 h in air. From the magneto-transport measurements, Ga-doped MnZn ferrites were found to have not only much lower resistivity values but also greatly improved LFMR ratios in comparison with undoped sample. The highest maximum LFMR ratio of 2.5% at 290 K in 0.5 kOe was achievable from 2 mol% Ga-doped MnZn ferrite. This large LFMR effect is attributable to an increase in spin electrons by Ga3+ ion substitution for the (Mn, Zn)2+ site.